UPAYA PERLINDUNGAN HUKUM BAGI NASABAH ASURANSI DI DESA GIRI MADIA KECAMATAN LINGSAR KABUPATEN LOMBOK BARAT - I GUSTI AGUNG WISUDAWAN; BUDI SUTRISNO; DIMAN ADE MULADA (LPPM PSDKU Kampus Mataram UNMAS Denpasar, 2022)
Insurance activities in Indonesia have progressed quite well, but there are several problems that arose and solutions were immediately sought, such as defaults, unsatisfactory services, complicated claim procedures and incomplete insured diseases. This research aims to find solutions and increase public awareness in utilizing insurance company services, especially in Giri Madia Village, Lingsar District, West Lombok Regency so that rural communities will avoid losses caused by insurance companies that fail to pay. The result is that the people of Giri Madia Village feel very helpful with the information about legal aspects in the insurance sector, problems and how to solve them.